Comparison of Pain Intensity in Mothers Undergoing Painless Delivery with and without Use of Entonox - Hasan Zabetian (Journal of Global Pharma Technology, 2017)
Introduction: Pain relief in pregnant women is regarded an important issue in obstetrics and gynecology. Labor pain can affect mother’s decisions for having children in the future, and naturally it can also be effective in family relationships. Therefore, identification of a safe and efficient method seems essential. This study aimed to compare the severity of labor pain in mothers undergoing painless delivery with and without the use of Entonox. Methods: This randomized double-blind study was conducted in Motahari Hospital in Jahrom, Iran. The random sampling was used here. The sample consisted of all pregnant women who wanted to have vaginal delivery based on gynecologist’s diagnosis. In this study, subjects were randomly divided into two groups of 40 people, including intervention (receiving Entonox) and control (control) groups. Data analysis was conducted using descriptive and inferential statistics using non-parametric Mann-Whitney and Friedman tests and SPSS version 18. Findings: The median age was 25 in the case group (receiving Entonox) and 26 in the control group (not receiving Entonox). The majority of pregnant women had one child. The most common side effects of Entonox in the intervention group included xerostomia (13, 39.4%) and drowsiness (10, 30.3%). Mann-Whitney test results showed that the labor pain levels in the intervention and control groups was significant at first, third, and fourth and fifth hours (p-value<0.05). Labor pain was not reported in fourth and fifth hours. Changes in patient’s vital signs (systolic and diastolic blood pressure, heart rate, and Spo2) the group receiving Entonox did not change significantly over time (hour one to five) (p-value>0.05).Conclusion: Findings showed that Entonox, as a safe method with fewer side effects for the mother and her baby during labor, has a higher potential compared other methods. Its analgesic effectiveness was considerably higher compared to other methods.Keywords: Entonox, Pain, Anesthesia